Quantifying the Demand, Supply, and Welfare Effects of Natural Disasters Using Monthly Trade Data - Gabriel J. Felbermayr; Jasmin Katrin Gröschl; Benedikt Heid (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We estimate the short-run trade effects of natural disasters using monthly trade data and data on the physical intensity of earthquakes and storms. We find large negative effects for heavily indebted poor, least developed or landlocked developing countries but only small effects for other economies. We use our estimates to identify key parameters of a dynamic quantitative trade model to disentangle the effects of disasters on supply, demand, and welfare and their spillovers on third countries via trade linkages. We apply our model to quantify the effects of the 1992 earthquake in Nicaragua, a small, heavily indebted poor country, and the 2011 Tohoku earthquake in Japan, a large developed economy. We find that spillovers are negligible if the country affected by a disaster is small but sizable for large economies. Similar disasters have heterogeneous effects on countries' demand and supply, highlighting the importance of event-specific policies in the aftermath of disasters.
Keywords: F14; F18; Q54; C68; 330; economic effects of natural disasters; monthly trade data; dynamic quantitative trade model; earthquakes; storms